Do anterior catheterizable urinary channels have fewer complications than posterior channels? An international cohort study. Issue 1 (February 2018) - Szymanski, K.M.; Lopez, P.-J.; Corbetta, J.P.; Reed, F.; Ruiz, J.; Pullin, Y.; Weller, S.; Zubieta, R.; Rink, R.C.; Cain, M.P.
Summary: Objective: Appendicovesicostomy (APV) and Monti ileovesicostomy (Monti) are durable catheterizable channels. While subfascial revision rates vary by channel type, a channel implanted in the anterior (vs posterior) aspect of the bladder may have a lower subfascial revision risk, due to decreased channel mobility and better fascial fixation. The present study aimed to compare long-term durability of anteriorly compared to posteriorly implanted APV and Monti channels in a large international cohort. Materials and methods: A retrospective cohort study was conducted on patients aged ≤21 years and who underwent APV or Monti surgery with an open technique at three high-volume centers (1990–2015). The following were noted: patient demographics, stomal and subfascial revisions, stomal location, channel placement (anterior/posterior), and channel type – APV, spiral Monti to umbilicus (SMU), other Monti channels. Survival analysis and Cox proportional hazards regression were used to separately examine the three channel groups. Results: Of the 675 patients who met inclusion criteria, 387 had an APV (71.3% anterior), 53 had an SMU (13.2% anterior) and 235 had other Monti channels (42.1% anterior). Median age at surgery was 8.8 years for APV (median follow-up: 5.5 years), 9.2 years for other Monti (follow-up: 6.6 years) and 7.9 years for SMU (follow-up: 9.0 years). Patients originated from the USA (67.9%), Argentina (26.4%) and Chile (5.8%). Overall, 76 stomal and 77 subfascial revisions occurred. Risk of stomal revision was 9.3–12.0% at 5 years of follow-up, and was similar between channel types or location ( P = 0.57). Risk of subfascial revision at 5 years was 7.4% for APV, 12.7% for all other Monti channels and 25.9% for SMU ( P = 0.001). On survival analysis, stomal and subfascial revision rates were similar between anterior and posterior channels for APV ( P ≥ 0.16), other Monti channels ( P ≥ 0.62) and SMU ( P ≥ 0.43) (Summary Fig.). On multivariate regression, channel configuration was not associated with stomal or subfascial revision for APV ( P ≥ 0.18) or other Monti channels ( P ≥ 0.64). Sex, age, diagnosis, country and stomal location were not associated with revision risk ( P ≥ 0.06). Discussion: Contrary to the hypothesis, subfascial revision rates were no different between anterior and posterior channels. Given that many reported outcomes related to genitourinary reconstruction occur rarely and require prolonged follow-up, collaborative research in this area should be encouraged. Conclusions: The study demonstrated durable long-term results with the APV and Monti techniques in an international cohort. Risks of stomal and subfascial complications were not significantly different between anteriorly and posteriorly implanted channels. As previously reported, Monti channels, particularly SMU, were more prone to undergoing subfascial revisions. Summary Fig Probability of remaining without subfascial revision, between anterior and posterior channels, for appendicovesicostomy (APV), other Monti channels, and spiral Monti to the umbilicus.